Essential Testing and Stepwise Evaluation of Lithium-Ion Battery Packs for Electric Vehicles: - - Mueangngoen, Sutthimat; Kumsuwan, Yuttana (ECTI Transactions on Electrical Engineering, Electronics, and Communications, 2025)
The evaluation of electric vehicle (EV) battery packs through essential testing is critical to prevent safety risks that may endanger technicians, users, and the battery itself, as well as to avoid undetected performance degradation. This paper presents a set of indispensable tests for assessing lithium-ion battery packs before their integration into EV systems. The important tests and their corresponding standards are summarized to stress the need for systematic evaluation and provide clear criteria for interpreting test results. A testing process is also proposed, beginning with the preparation and verification of battery management system data, which includes the acquisition and analysis of key parameters for the initial evaluation of potential faults. Electrical tests are then carried out, including open-circuit voltage measurement, short circuit inspection, insulation resistance testing, withstand voltage testing, and internal resistance measurement, all aimed at verifying the safety and detecting possible defects. This is followed by discharging and charging tests to record characteristic behaviour and to validate capacity, state of charge, and state of health for performance assessment. Finally, the proposed procedure is demonstrated on a 33.6-kWh-100S1P LiFePO4 battery pack, using industrial-grade electrical testing equipment and a 150-kW programmable power supplies, providing a practical reference for test engineers.